HYDROLOGICAL EFFICIENCY OF WATER STORAGE TECHNOLOGIES IN ARID REGIONS - Eshmanov Husniddin Narzulla o’g’li (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This study investigates the hydrological efficiency of various water storage  technologies  implemented  in  arid  and  semi-arid  regions  to  mitigate  water scarcity. It examines how these technologies affect water conservation, groundwater recharge,  and  surface  water  availability.  Field  measurements  and  hydrological modeling  were used to  assess  the  performance  of  reservoirs, check  dams, and  soil moisture retention methods. The results demonstrate significant improvements in water availability  and  ecosystem  sustainability.  Recommendations  for  optimizing  water storage  infrastructure  to  enhance  hydrological  efficiency  in  dry  environments  are discussed.